1995
DOI: 10.1128/jvi.69.7.4189-4197.1995
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral compound enviroxime targets the 3A coding region of rhinovirus and poliovirus

Abstract: Enviroxime is an antiviral compound that inhibits the replication of rhinoviruses and enteroviruses. We have explored the mechanism of action of enviroxime by using poliovirus type 1 and human rhinovirus type 14 as model systems. By varying the time of drug addition to virus-infected cells, we determined that enviroxime could be added several hours postinfection without significant loss of inhibition. This suggested that the drug targeted a step involved in RNA replication or protein processing. To identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 69 publications
1
85
0
Order By: Relevance
“…Different viruses, even within the Picornaviridae family, appear to use different strategies to recruit PI4KIII␤ (42,46,47). As has been found by others (40,59), we identified resistance mutations in HRV's 3A protein upon sequential passaging of virus in the presence of increasing concentrations of compounds from our PI4KIII␤ inhibitor series. The I42V resistance mutation in 3A was the first evidence that the mechanism of action of the compound series under investigation was similar to the mechanism of action of enviroxime.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Different viruses, even within the Picornaviridae family, appear to use different strategies to recruit PI4KIII␤ (42,46,47). As has been found by others (40,59), we identified resistance mutations in HRV's 3A protein upon sequential passaging of virus in the presence of increasing concentrations of compounds from our PI4KIII␤ inhibitor series. The I42V resistance mutation in 3A was the first evidence that the mechanism of action of the compound series under investigation was similar to the mechanism of action of enviroxime.…”
Section: Discussionsupporting
confidence: 70%
“…Population sequencing revealed that the resistant variants all contained a single-nucleotide mutation encoding the substitution I42V in the HRV 3A protein. This same mutation has been previously reported to confer resistance to enviroxime, an antipicornaviral agent that acts at the stage of viral RNA replication (40). The I42V mutation was reverse engineered into the full-length HRV-B14 replicon, and virus was produced.…”
Section: Screening Of a Diverse Subset Of The Proprietary Collection mentioning
confidence: 77%
“…Recently, we demonstrated that enviroxime inhibits HCV subgenomic replicon replication [79]. Picornaviruses that are resistant to enviroxime carry mutations in protein 3A [80]. The picornavirus protein 3A is a membrane associated protein that is involved in the formation of the membranous web.…”
Section: Pi4kiiis: Promising Targets For Therapeutic Intervention?mentioning
confidence: 99%
“…245 In particular the 3A protein, which is involved in the initiation of plus strand RNA synthesis, was implicated as likely target of drug activity. 246,247 However, results from another study suggest that enviroxime targets a complex of proteins and/or cellular factors and that the exact mechanism remains to be studied. 248 Although there was a statistically significant reduction in clinical score in a prophylactic study with HRV-9-infected volunteers, 152 enviroxime failed in experimentally induced HRV-4 and HRV-39 infection, 149,151 and in clinical studies, [248][249][250] because of poor bioavailability and side effects.…”
Section: Inhibition Of Viral Rna Synthesismentioning
confidence: 99%